Graphene oxide-zinc oxide nanocomposite modified disposable electrodes for detection of uric acid in fetal bovine serum - Yildirim, Ayla; Maral, Meltem; Zaman, Buse Tugba; Bozoglu, Aysen; Demir, Cansu; Bakirdere, Sezgin; Erdem, Arzum (ELSEVIER SCIENCE SA, 2024)
Uric acid (UA) is the end product of purine metabolism, which is involved in many physiological processes in humans. This compound is produced daily in the human body and the excess is excreted in urine. For various reasons, uric acid in human serum that is lower or higher than the reference range causes some diseases such as liver diseases, nephritis, multiple sclerosis and diabetes. Hence, determination of UA at trace levels is very crucial. Here, a pencil graphite electrode (PGE) modified with graphene oxide-zinc oxide (GO-ZnO) nanocomposite was used to develop an electrochemical biosensor (GO-ZnO/PGE) for UA detection. The prepared GOZnO modified electrodes was characterized by scanning electron microscopy (SEM), Energy-Dispersive X-Ray Spectroscopy (EDX), Electrochemical Impedance Spectroscopy (EIS) and Cyclic Voltammetry (CV). It was revealed that the existence of ZnO in the GO-ZnO/PGE largely enhanced the surface area and increased its sensitivity for electrochemical sensing of analyte. The uric acid biosensor exhibited voltammetric peaks in the differential pulse voltammetry (DPV) measurements, allowing electrochemical detection of UA. The detection limit of UA was found to be 2.56 mu M in buffer medium in the range of 10-100 mu M UA. The detection limit of UA was found to be 4.76 mu M in 1:1000 diluted FBS medium in the range of 10-100 mu M of UA. The GO-ZnO/PGE provided the results in good reproducubility based on electrochemical measuruments while detecting UA. Furthermore, selectivity tests were also performed in FBS medium containing possible interferents such as ascorbic acid (AA) and Glucose (Glu), demonstrating the applicability of GO-ZnO modified electrodes. Sensitivity was calculated for phosphate-buffered saline (PBS) and fetal bovine serum (FBS) mediums and found to be 0.22 and 0.47 mu A mu g-1 mL cm-2, respectively, which validates the good sensitivity of the GO-ZnO/PGE electrodes.
Keywords: Graphene oxide; Zinc oxide; Electrochemical biosensor; Uric acid detection; Fetal Bovine Serum; ELECTROCHEMICAL DETECTION; ASCORBIC-ACID; DOPAMINE; BIOSENSOR; SENSORS; ENZYME; FILM; Chemistry; Electrochemistry